Asymptomatic carotid stenosis: intervention or best medical therapy? - Gaba, Kamran; Ringleb, Peter A.; Halliday, Alison (Current neurology and neuroscience reports, 2018)
Purpose of ReviewProvide a current overview regarding the optimal strategy for managing patients with asymptomatic carotid artery stenosis.Recent FindingsCarotid endarterectomy (CEA) and carotid artery stenting (CAS) reduce long-term stroke risk in asymptomatic patients. However, CAS is associated with a higher risk of peri-procedural stroke. Improvements in best medical therapy (BMT) have renewed uncertainty regarding the extent to which results from older randomised controlled trials (RCTs) comparing outcomes following carotid intervention can be generalised to modern medical practise.Summary‘Average surgical risk’ patients with an asymptomatic carotid artery stenosis of 60-99% and increased risk of late stroke should be considered for either CEA or CAS. In patients deemed ‘high risk’ for surgery, CAS is indicated. Use of an anti-platelet, anti-hypertensive and statin, with strict glycaemic control, is recommended. Results from ongoing large, multicentre RCTs comparing CEA, CAS and BMT will provide clarity regarding the optimal management of patients with asymptomatic carotid artery stenosis.
Gesehen am 01.08.2019